Students’ Perception: Using Android-based Exam Browser as the Medium to Assess Examination - Irnawati Irnawati; Henny Yulia; Novarita Novarita (JOLE (Journal of Language Education), 2023)
This study was to find out the students’ perception on the use of Android- based ExamBrowser as the medium to assess examination. This study used the qualitative survey method.The population of the study was the eighth and ninth grade students of SMPIT Tunas CendikiaBaturaja. The writer took all of the sample by applying total sampling consist of 85 students.The data collected through questionnaire, it consists of 35 statements. Then, the writer usedpercentage formula to analyze the data. The result of this study showed that there were manystudents who think that they were agree or had positive perception on the use of Android-based exam browser as the medium to assess examination in SMPIT Tunas Cendikia Baturaja.The data were in high criteria in each indicator. Students' interest/intention from the eighthgraders (73,62%) and the ninth graders (64,90%), students' perceived usefulness from theeighth graders (74,07%) and the ninth graders (56,46%), students' perceived of ease of usefrom the eighth graders (59,26%) and the ninth graders (58,33%) and students' Androidattitude from the eighth graders (68,52%) and the ninth graders (60,20%). From the result,students’ anxiety from the nineth grade (44,39%) disagree or indicate to negative perceptionabout the use of Android-based exam browser as the medium to assess examination in SMPITTunas Cendikia Baturaja. It was because Android-based Exam Browser still intimidated andmade them feel afraid of making mistakes in using Android- based exam browser, beside thatalso anxious and nervous due to sometimes their Android did not as friendly as hangs, runsout of battery, and disconnected from the connection server.